Enhanced capacity of women in using climate smart agriculture technologies - Akpoffo, Marius; Koné, Pierre; Dossou-Yovo, Elliott Ronald (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
On March 14th in Siramana and March 19th in Selingue, two workshops were held to enhance women's skills in climate smart agriculture technologies. The workshops focused on Smart-Valleys approach for water control in inland valleys, alternate wetting and drying for producing rice with less water and greenhouse gas emissions in irrigated systems, and improved access to input, information, and markets using multiple stakeholders' platforms. The workshops were attended by 25 leaders from women's farmer organizations and were followed by back-up activities to help participants implement the CSA technologies in their specific fields, serving as demonstrations for members of their organizations.